KOORDINASI SISTEM RESPONSE TIME MUSIBAH PELAYARAN DI KANTOR SEARCH AND RESCUE (SAR) PONTIANAK - Novi Pristian Wulandari E.21111111 (FISIP Universitas Tanjungpura, 2013)
The writing of this article aims to illustrate how internal coordination is done vertically and horizontally in the Office of Pontianak in the implementation of disaster management response time cruise disaster in West Kalimantan and constraints faced in handling shipping disaster. This study included in the descriptive study with qualitative analysis, which focuses on internal coordination variable vertical and horizontal internal coordination. The results of the field study showed that internal coordination within the system response time cruise disaster on disaster management office Pontianak implemented vertical relationships and horizontal relationships. Internal coordination system had been implemented optimally and in accordance with the rules and procedures have been established and continue to coordinate with external parties such as the potential of regional institutions, private and public. To anticipate an increase in the number of disasters that have not been handled in the need for additional primary facilities and support for the implementation of search and rescue operations at sea in order to increase the number of calamity that handled and the number of victims could be saved. Keywords: Response Time, Internal Coordination Vertical, Horizontal Internal Coordination and Disaster Handling Constraints.